O processo histórico de reforma agrária na Fazenda Annoni: da desapropriação à (re)apropriação privada - Dickel, Simone Lopes (2021)
This thesis focuses on the historical process of agrarian reform at the Annoni farm in northern Rio Grande do Sul, understood as a dynamic and multifaceted social construction. The historical process of agrarian reform at the Annoni farm brings together a multitude of experiences, formed from certain material circumstances, which engender a distinct response from the subjects to everyday issues, since they act based on certain guiding principles that constitute the social being. In order to contemplate the three decades that have passed since the establishment of the settlements, we consider it pertinent to establish the post-1985 context as the initial landmark, encompassing the land titling process that began in 1991 and is still ongoing. As the final landmark, we establish the year 2015, in order to highlight some possible developments in the agrarian reform process, in view of the political changes that signal a process of retraction of the agrarian reform, after some important achievements by the peasants. Seeking to understand the agrarian reform process in its concreteness, the discussions pertinent to this thesis revolve around the tripod that characterizes the space of the Annoni settlements: the emergence of a generational issue; the private (re)appropriation of land, with the titling process; and the socio-spatial dynamics, which reflect the interrelationship between these two processes. Based on these constituent elements of the agrarian reform process, which was created in the absence of a "hegemonic" project, we believe it is pertinent to characterize the Brazilian State's agrarian reform project (an instrument of passive revolution) and the popular agrarian reform project (MST), which were involved in a symbolic dispute in the context of the implementation of the settlements, identifying, in addition to the differences between them, some possible gaps that constitute them. And it is in the face of these gaps, in the daily implementation of agrarian reform, that new challenges arise and that the settlers seek to implement their own projects, in line with the family's expectations regarding agrarian reform, but under the influence of certain material circumstances. Based on the analysis of titling processes and other INCRA sources, it was possible to understand a multiplicity of family trajectories that reinforce the role of the individual in the historical process, making agrarian reform a complex social construction, beyond the expectations of its agents.